Photoelectrochemical analysis of band gap modulated TiO2 for photocatalytic water splitting. (13th April 2017) - Saraf, Shashank; Giraldo, Manuel; Paudel, Hari P.; Sakthivel, Tamil S.; Shepard, Cathrine; Gupta, Ankur; Leuenberger, Michael N.; Seal, Sudipta
Abstract: In this study the photocatalysis efficiency of titania (TiO2 ) is increased by conjugating it with folic acid (FA) molecules through a silane linker (APTMS) layer. Electrochemical testing demonstrated higher negative open circuit potential (OCP) in surface engineered TiO2 as compared to TiO2 indicating higher Schottky barrier leading to suppressed electron–hole pair recombination. The photocurrent density under no bias conditions demonstrated 55% increase in modified titania due to lower band gap and suppressed electron hole pair recombination. The mechanism behind higher photocatalytic properties of surface engineered TiO2 was derived using density functional theory (DFT). Graphical abstract: Scheme depicting the mechanism of electron hole pair formation using TiO2 -APTMS-FA for water splitting. The band gap energy Eg of TiO2 is 3.2 eV. Photons with energy larger than the HOMO/OV–LUMO gap (ħω1  > 2.0 eV) get absorbed by OV/APTMS/FA. Note that the HOMO state is hybridized with the OV band of TiO2 at the surface. The holes that are left behind in the HOMO/OV state are filled by e-h pair generation from the TiO2 valence band (VB) to the HOMO-OV state by photons (ħω2  > 2.5 eV). Regular e–h pair generation in the conduction band (CB) and VB takes place through absorption of photons with ħω3  > Eg . The green parts of the band bending represent the extra potential barrier coming due to the surface modifications. Image 1 Highlights: TiO2 is linked to FA through a linker molecule APTMS. Increased oxygen vacancies, and n-type conductivity. 55% increase in photocurrent than TiO2 alone and P25. The enhancement of the TiO2 photocatalytic system specific to water spitting.